Flavor characterization of top blade, top sirloin, and tenderloin steaks from A- and B-maturity carcasses of high and normal pH - E.J. Yancey; Michael E. Dikeman; K.A. Hachmeister; Edgar Chambers IV; George A. Milliken; E. Westcott (Kansas Agricultural Experiment Station Research Reports, 2003)
The infraspinatus muscle (top blade steak) from the chuck clod, the gluteus medius muscle (top sirloin steak) from the sirloin, and the psoas major muscle (tenderloin steak) from the loin were obtained from A- and B-maturity carcasses with either low-Slight or Small marbling and with either normal ultimate pH (5.7 or less) or high pH (6.0 or higher) to evaluate flavor profile characteristics. Muscles were aged for 7, 14, 21, and 35 days. A highly trained flavor-profile sensory panel evaluated charbroiled steaks from these muscles. Muscles from high pH (dark cutting) carcasses had less typical beef flavor identity and less brown roasted flavor than those from carcasses with normal pH. Top blade steaks had a more intense bloody/serumy flavor than top sirloin and tenderloin steaks. Aging steaks to 21 or 35 days postmortem increased the metallic flavor sensory characteristic. Top sirloin steaks had a more intense sour flavor than top blade or tenderloin steaks, and steaks from carcasses having a high pH were found to be more rancid than those from carcasses with normal pH. In general, high pH steaks and those aged longer than 21 days had less desirable flavor profiles than normal pH steaks and those aged only 14 days.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Maturity; pH